2005
DOI: 10.1016/j.femsec.2004.10.005
|View full text |Cite
|
Sign up to set email alerts
|

N-hexanoyl-l-homoserine lactone, a mediator of bacterial quorum-sensing regulation, exhibits plant-dependent stability and may be inactivated by germinating Lotus corniculatus seedlings

Abstract: The half-life of N-hexanoyl-l-homoserine lactone (C6-HSL) was determined under various pH and temperature conditions, and in several plant environments. C6-HSL was sensitive to alkaline pH, a process that was also temperature-dependent. In addition, C6-HSL disappeared from plant environments, i.e. axenic monocot and dicot plants cultivated under gnotobiotic, hydroponic conditions, albeit with variable kinetics. The disappearance was rapid at the root system of legume plants such as clover or Lotus, and slow or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
89
0
5

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 117 publications
(99 citation statements)
references
References 28 publications
(54 reference statements)
5
89
0
5
Order By: Relevance
“…The effect of pH on the abiotic degradation of AHLs in aqueous media (LB media, organic buffers or pure water) is well established: AHLs degrade more rapidly at higher pH , Delalande et al 2005. In seawater, with an average pH of 8.2, AHLs are expected to degrade quite rapidly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of pH on the abiotic degradation of AHLs in aqueous media (LB media, organic buffers or pure water) is well established: AHLs degrade more rapidly at higher pH , Delalande et al 2005. In seawater, with an average pH of 8.2, AHLs are expected to degrade quite rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that AHLs are very short-lived in aqueous media with pH in the range of seawater . Furthermore, it appears that AHLs are also degraded enzymatically in natural systems (Delalande et al 2005, Wang & Leadbetter 2005, a process that has been termed "quorum quenching".…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In airway epithelia, PON2 appears to be the most efficient degrader of 3-oxo-C12-HSL and consequently is considered likely to contribute to host defences against bacteria such as P. aeruginosa (Stoltz et al, 2007). Germinating seedlings of the leguminous plant Lotus corniculatus have also been shown to be capable of enzymically inactivating a wide range of AHLs, although the mechanism involved has yet to be established (Delalande et al, 2005).…”
Section: Eukaryote-mediated Quorum Activation and Quenchingmentioning
confidence: 99%
“…Teplitski et al have shown that various species of higher plants, including pea seedlings, secrete a series of unidentified signals that are capable of interfering with the quorum-sensing behavior of several bacterial reporter strains (49). This would suggest that plants may have evolved mechanisms to interfere with or respond to bacterial quorum sensing and thereby have the potential to manipulate the behavior of the associated bacteria to their advantage (8,20,34,49).…”
mentioning
confidence: 99%